Psychiatric morbidity among pregnant and non pregnant women in Ibadan, Nigeria (2023)
A comparative cross-sectional study was conducted among 991 pregnant and 674 non-pregnant women of reproductive age attending healthcare facilities in Ibadan, Nigeria using the General Health Questionnaire-12 (GHQ), and WHO self-reporting questionnaire (SRQ). Logistic regression analysis was conducted to identify predictors of psychiatric morbidity at p <0.05. A significantly higher proportion of pregnant women experienced psychological distress on the GHQ (51.8%) and psychiatric morbidity on SRQ (33.3%) compared with 28.6% and 18.2% of non-pregnant women, respectively. Predictors of psychiatric morbidity among pregnant women were the type of facility, poor satisfaction and communication with partners, the experience of violence in the home, previous abortions, and previous history of depression. Psychiatric morbidity among non-pregnant women was predicted by younger age, previous history of depression, poor satisfaction and communication with partners. There is a need for early identification of psychiatric morbidity among women of reproductive age, to ensure early interventions and prevent long-term disability.